Acute toxicity of chlorpyrifos to embryo and larvae of banded gourami Trichogaster fasciata. Issue 2 (1st February 2017) - Sumon, Kizar Ahmed; Saha, Sampa; van den Brink, Paul J.; Peeters, Edwin T.H.M.; Bosma, Roel H.; Rashid, Harunur
ABSTRACT: This study elucidated the acute toxicity of chlorpyrifos on the early life stages of banded gourami ( Trichogaster fasciata ). To determine the acute effects of chlorpyrifos on their survival and development, we exposedthe embryos and two-day-old larvae to six concentrations (0, 0.01, 0.10, 1.0, 10 and 100 µg L −1 ) of chlorpyrifos in plastic bowls. Log-logistic regression was used to calculate LC10 and LC50 values. Results showed that embryo mortality significantly increased with increasing chlorpyrifos concentrations. The 24-h LC10 and LC50 values (with 95% confidence limits) of chlorpyrifos for embryos were 0.89 (0.50–1.58) and 11.8 (9.12–15.4) µg L −1, respectively. Hatching success decreased and mortality of larvae significantly increased with increasing concentrations of chlorpyrifos. The 24-h LC10 and LC50 values (with 95% confidence limits) of chlorpyrifos for larvae were 0.53 (0.27–1.06) and 21.7 (15.9–29.4) µg L −1, respectively; the 48-h LC10 and LC50 for larvae were 0.04 (0.02–0.09) and 5.47 (3.77–7.94) µg L −1, respectively. The results of this study suggest that 1 µg L −1 of chlorpyrifos in the aquatic environment may adversely affect the development and the reproduction of banded gourami. Our study also suggests that banded gourami fish can serve as an ideal model species for evaluating developmental toxicity of environmental contaminants.